2008
DOI: 10.1111/j.1525-1594.2008.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Atrial Natriuretic Peptide Levels During Cardiac Bypass in the Fetal Goat

Abstract: The aim of this study is to evaluate the effect of fetal cardiac bypass on the production and secretion of fetal atrial natriuretic peptide (ANP) in the goat. Eighteen pregnant goats, at days 120 to 140 of gestation, were randomly divided into control (n = 8) and bypass (n = 10) groups. The control group underwent a sham procedure involving fetal sternotomy and cannulation. The bypass group underwent fetal cardiac bypass using a centrifugal pump for 30 min. Fetuses in the bypass group exhibited hypoxia, hyperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Zhou et al . associated increased plasma TnI with depressed myocardial function in a fetal goat model 21. In support of these findings, the present study detected TnI degradation in the fetal heart by immunoblot of myocardial homogenates.…”
Section: Discussionsupporting
confidence: 87%
“…Zhou et al . associated increased plasma TnI with depressed myocardial function in a fetal goat model 21. In support of these findings, the present study detected TnI degradation in the fetal heart by immunoblot of myocardial homogenates.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the Tei index increased significantly in the ventricles post-arrest (P<0.05). Similarly, in a late third-trimester goat model, LV and RV myocardial dysfunction was observed (30), with an increased Tei index value 1 h after CPB. The separate evaluation of RV and LV dysfunction provides information on the sensitivity of each ventricle to hemodynamic alterations during bypass, which may then affect fetal blood composition (29).…”
Section: Discussionmentioning
confidence: 77%
“…This leads to difficulties in performing standard echocardiographic measurements of ventricular function in the ovine fetus, due to distorted ventricular geometry, preload and afterload (11). By contrast, the Tei index applies nongeometric assessment and overcomes such difficulties inherent to geometric assessment of LV and RV function (30). This suggests that it is a sensitive indicator of fetal ventricular dysfunction following cardioplegic arrest, particularly in the evaluation of ventricular dysfunction post-bypass.…”
Section: Discussionmentioning
confidence: 99%
“…43 More recently, it was shown that fetal bypass leads to cardiac injury, reflected in troponin elevation and increased plasma natriuretic peptides. 55 Calcium-handling properties of the fetal myocardium differ from the more mature state, and recent studies have started to define strategies for myocardial protection during fetal open heart surgery. 51,52 …”
Section: Fetal Cardiac Function and The Fetal Stress Responsementioning
confidence: 99%